Eksaminasi Putusan Peninjauan Kembali Mahkamah Agung dalam Koreksi Kekhilafan Hakim (Judex Facti) Pada Perkara Narkotika (Studi Putusan: Nomer 2473/PK/Pid.Sus/2025) - Melinda , Najwa; Fakhlur, Fakhlur (Postulat, 2026)
This study examines the role of judicial review (Peninjauan Kembali/PK) as a corrective mechanism for judicial error in narcotics cases, focusing on Supreme Court Decision Number 2473 PK/Pid.Sus/2025. Using normative legal research and case analysis, the study finds that the Supreme Court identified errors in the judex facti’s assessment of legal facts and sentencing proportionality, particularly regarding the quantity of evidence and the offender’s role. Consequently, the sentence was reduced from 13 years to 9 years of imprisonment. This decision reflects the application of substantive justice by prioritizing proportionality and material truth while maintaining legal certainty.